2012
DOI: 10.4103/0975-9476.104430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Polyherbal Unani formulation in acne vulgaris: A preliminary study

Abstract: Acne vulgaris is the most common disorder treated by dermatologists. Acne is a disease of pilosebaceous units characterized by the formation of the open and closed comedones, papules, pustules, nodules and cysts. A preliminary trial was conducted in the department of Medicine, National Institute of Unani Medicine, Bangalore, India, to assess the safety and efficacy of a Polyherbal Unani Formulation (PHUF) in the management of Acne Vulgaris on scientific parameters. Twenty five patients, diagnosed with acne, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…This study is in accordance with the study of Lone et al, they used a Polyherbal Unani formulation and reported improvement at P < 0.001. [ 16 ] The present study is also in accordance with study by Parveen et al, they also found role of Unani herbomineral cream significant in reducing Acne vulgaris. [ 29 ]…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study is in accordance with the study of Lone et al, they used a Polyherbal Unani formulation and reported improvement at P < 0.001. [ 16 ] The present study is also in accordance with study by Parveen et al, they also found role of Unani herbomineral cream significant in reducing Acne vulgaris. [ 29 ]…”
Section: Discussionsupporting
confidence: 92%
“…Acne vulgaris is characterized by the formation of open and closed comedones, papules, pustules, nodules and cysts. [ 1 4 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. incidus is known to scavenge free radicals produced by P. acnes (Jain and Basal, ), and C. longa has antimicrobial activities (Ammon and Wahl, ). A polyherbal Unani formulation also demonstrated promising therapeutic effects (Lone et al ., ). This consisted of Iris florentina , A. indica leaves, Acacia speciosa bark, and Abrus precatorius ; the authors state that this combination has antiinflammatory and antimicrobial properties.…”
Section: Discussionmentioning
confidence: 97%
“…Six studies were reviewed, which evaluated topical or herbal preparations from Ayurveda (Paranjpe and Kulkarni, ; Lalla et al ., ), Unani (Lone et al ., ), Kampo (Kim and Kim, ), and traditional Chinese medicine (Pan, ; Liu et al ., ). These formulations are composed of multiple herbs with complementary therapeutic mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%